2017
DOI: 10.2298/sos1704445c
|View full text |Cite
|
Sign up to set email alerts
|

Activated sintering of Tungsten heavy alloy

Abstract: In the present work, characterization of sintering behavior of Tungsten heavy alloy has been done through powder metallurgy route using Spark plasma sintering (SPS). Fine powder of Tungsten (<30 µm) was separately mixed with Ni, Co, Fe, Mo and Cu each with 1 weight%. Spark Plasma Sintering (SPS) technique (1200°C, 20 MPa pressure with 1 min holding time) was used to sinter the mixed powders. The maximum density was observed in W-Ni followed by Co, Fe, Cu, Mo and with least in pure tungsten sample. Optical micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…8a and b) [16,[60][61][62][63]. For instance, Hwan-tae et al [64] observed a temperature difference more than 130 o C between the center and periphery surface of nickel sample at the maximum temperature of 930 o C. In the SPS tools, the temperature of the die is usually measured by a thermocouple [66] or pyrometer [53]. In fact, there is no scalable method to measure the exact temperature in various regions of the sample and validate the simulation results.…”
Section: Temperature Distributionmentioning
confidence: 99%
“…8a and b) [16,[60][61][62][63]. For instance, Hwan-tae et al [64] observed a temperature difference more than 130 o C between the center and periphery surface of nickel sample at the maximum temperature of 930 o C. In the SPS tools, the temperature of the die is usually measured by a thermocouple [66] or pyrometer [53]. In fact, there is no scalable method to measure the exact temperature in various regions of the sample and validate the simulation results.…”
Section: Temperature Distributionmentioning
confidence: 99%
“…Annealing nanostructured materials at elevated temperatures causes changes in their microstructure, leading to changes in their physical and chemical properties [12][13][14][15][16][17][18][19][20][21][22][34][35][36]. At temperatures below the crystallization temperature, the alloy undergoes structural relaxation, whereas amorphous phase crystallization and nanocrystalline grain growth occur at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…At temperatures below the crystallization temperature, the alloy undergoes structural relaxation, whereas amorphous phase crystallization and nanocrystalline grain growth occur at higher temperatures. These changes affect mechanical, electrical and magnetic properties, corrosion resistance, thermal stability, and catalytic activity [12][13][14][15][16][17][18][19][20][21][22][34][35][36].…”
Section: Introductionmentioning
confidence: 99%